REBRANDING UNIVERSITAS KATOLIK DARMA CENDIKA - Marchelina Alensia; Melissa Angga; Tyrza Adelia (CALYPTRA, 2018)
The rebranding of Universitas Katolik Darma Cendika is done to build UKDC's brand accurately, based on its target market which belongs to generation Z. A literature study about supporting theories is done before the rebranding process. After that comes the analysis process, and it is known that the current UKDC brand is not relevant enough to the target market, and UKDC hasn't accentuate its uniqueness enough. Through requirement analysis, it is concluded that UKDC's brand needs to form the right positioning corresponding to its uniqueness, and build a relevant brand to the tarhet market. After that, analysis to form the new positioning is done. The design process is divided into two, the design concept and design process. The design concept is assigned to ensure unity in all the design. Based on the positioning and design concept, the design process is started. The design process consists of logo, tagline, graphic pattern, website, stationery, and brand identity guidelines design. The designs are implemented in the form of website, stationery, and brand identity guidelines. The next step is experiment and evaluation, which consist of verification and validation. The validation process is done into two types of respondents, the target market and designer. Based on the experiment and evaluation process it is concluded that the rebranding of UKDC has succeed in increasing the target market's interest, and becoming a more relevant brand to the generation.